Expert‐Derived Flood Damage Curves for Critical Infrastructure Network Components - James H. Williams; Huong Ngan Vu; Ryan Paulik; Conrad Zorn; Liam Wotherspoon (Journal of Flood Risk Management)
ABSTRACT Flood impact assessment is limited by a scarcity of damage curves for critical infrastructure network components. This study presents a judgement‐based methodology for developing critical infrastructure network component flood damage curves. The 12 semi‐structured workshops record responses for estimated minimum and maximum damage ratios at 0.5, 1, 2 and 3 m water depths. The 46 responses, weighted by participant expertise level, are aggregated into a discrete minimum and maximum damage curve for each component. Damage curves are presented for 34 infrastructure network components across the transportation, energy, water, and telecommunication sectors. These damage curves are benchmarked against relevant flood damage curves from previous studies, providing insight on how flood damage models compare internationally and across methods. While the synthesised flood damage curves allow for nationally consistent risk assessments, this study highlights the need for flood damage curves that represent local risk contexts for infrastructure network components to facilitate locally applicable risk assessments that inform risk management.